Active Labor Market Policies in the OECD and in Selected Transition Economies - Lehmann, Hartmut 1995- (The World Bank, 1999)
August 1995 - Applying mechanically active OECD labor policies in Hungary, Poland, and Russia makes no sense because the economies are so different. Which labor policies are realistic there? Training able workers in scarce, needed skills; easing credit for (and thereby encouraging) the self-employed; giving public jobs to problem workers and the long-term unemployed; and improving consultation services for the unemployed. Transition economies have introduced a range of OECD active labor market policies to combat unemployment - albeit often on paper only, as with rising unemployment passive policies have crowded out active ones. But even in the Czech Republic, active labor market policies have contributed only marginally to reducing unemployment. One task for policymakers in Central and Eastern Europe must be to convey the message that, even under the best circumstances, active labor policies can play only a marginal role in reducing unemployment. OECD labor policies cannot be applied mechanically in Central and Eastern Europe because the situation there is different. Severe and persistent shortages in capital and managerial ability are sure to keep labor demand weak in the medium term, while labor supply will be abundant. As enterprises are restructured and liquidated, the newly unemployed workers cannot be absorbed by the weak private sector and must compete for scarce jobs. Women and older, less educated men have particular trouble finding work. Which active labor policies does Lehmann suggest might be effective? Limited funds for active labor policies might best be spent retraining the most able unemployed workers to develop skills needed in the private sector. Public employment programs might be targeted especially to problem groups of workers and to the long-term unemployed - more for reasons of equity than of efficiency.